The Algorithmic Cradle: Should AI Be Used in Reproductive Medicine? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming clinical practice, and few fields present a more complex and ethically ...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Medical Ethics